Risky sexual behaviours among female in-school adolescents in Delta, Nigeria: self-esteem, parental involvement and religiosity as predictors (2014)
This study adopted descriptive survey design of ex post type to examine the extent to which self-esteem, parental involvement and religiosity predicted risky sexual behaviours among female in-school adolescents in Delta state, Nigeria. Four hundred adolescents whose age ranged from 15 to 19 (SD=17.37) were drawn using Multi-stage sampling technique. Three standardized and one researcher developed self-report measures were used for data collection. Pearson Product Moment Correlation and regression statistics were used to analyze data at 0.05 level of significance. Self-esteem, parental involvement and religiosity have negative relationship with participants’ risky sexual behaviours. The independent variables accounted for 30.3% of the variance in prediction of risky sexual behaviour. Self-esteem made the highest contribution to the prediction of risky sexual behaviour of adolescents while parental involvement made the least contribution. The need for Programme designers, sexuality educators, and Counsellors to incorporate these variables into activities to delay sexual debut by adolescents was implied from this outcome.